Awareness level, knowledge and attitude towards breast cancer among staff and students of Hail University, Saudi Arabia - Almeshari, Meshari; Alzamil, Yasser; Alyahyawi, Amjad; Abanomy, Ahmad; Althmali, Omar; Al-Enezi, Mamdouh S.; G., ShashiKumar C.; Osman, Hamid; Khandaker, Mayeen Uddin * (PLOS, 2023)
Introduction Awareness of screening procedures and illness warning signals is critical for expanding and implementing screening programs in society, which would improve the odds of early identification of breast cancer.